The Effectiveness of Statistical Analytical Review as a Substantive Auditing Procedure: A Simulation Analysis. - Knechel, W. Robert (The Accounting Review, 1988)
ABSTRACT: The purpose of this paper is to assess via simulation the effectiveness of various analytical review procedures when used in combination with a partitioned approach to dollar unit sampling for tests of account details. Seven analytical review procedures based on regression analysis were applied to two sets of simulated accounting data which were seeded with different patterns of known overstatement errors. Audit sample sizes for dollar unit sampling and achieved audit detection risk were then computed based on the analytical review outcomes. There were three major findings in this study. First, regression based analytical review increased audit effectiveness relative to an audit strategy that did not use analytical review. Second, the use of monthly data greatly increased the effectiveness of analytical review. Finally, regression based analytical review models were very efficient in detecting potentially material misstatements.